Career Intervention Considerations for Unwed Young Black Mothers in the United States. Issue 2 (3rd October 2013) - Prescod, Diandra J.; Daire, Andrew P.
Abstract : Teen pregnancy among unwed young Black mothers is still an issue of concern in the United States. Black teen mothers face educational, economic, and career/vocational challenges. This article discusses integratingGottfredson's (1981) career theory and the Outline for Cultural Formulation (American Psychiatric Association, 1994 ) in career development counseling with young Black mothers.